Mandatory fortification with folic acid in the United States appears to have adverse effects on histone methylation in women with pre-cancer but not in women free of pre-cancer - Chandrika J Piyathilake; Maurizio Macaluso; Jorge E Celedonio; et al (Dove Medical Press, 2009)
Chandrika J Piyathilake1, Maurizio Macaluso2, Jorge E Celedonio1, Suguna Badiga1, Walter C Bell3, William E Grizzle31Department of Nutrition Sciences, 2School of Public Health, 3Department of Pathology of The University of Alabama at Birmingham, AL, USAObjective: To evaluate whether mandatory fortification of grain products with folic acid in the US is associated with changes in histone methylation in cells involved in cervical carcinogenesis.Methods: Cervical specimens obtained before (1990 to 1992) and after mandatory folic acid fortification (2000 to 2002) were used to examine the degree of histone methylation (H3 Lys-9) by immunohistochemistry. 91 women (51 before and 40 after fortification) were diagnosed with cervical intraepithelial neoplasia (CIN) grade 3 or carcinoma in situ (CIS) and sections utilized in the study also contained normal, reactive or metaplastic cervical epithelium, CIN 1 or CIN 2. 64 women (34 before and 30 after fortification) were free of CIN and these sections contained only normal or reactive cervical epithelium. Immunohistochemical staining for H3 Lys-9, its assessment in different cell or lesion types and data entry were blinded for fortification status. For each cell type or lesion category we used PROC MIXED in SAS with the specimen identifier as a random effect and the robust variance estimator to estimate age- and race-adjusted intensity score for H3 Lys-9 in the pre- and post-fortification periods.Results: Degree of H3 Lys-9 methylation was significantly higher (P < 0.0001) in ≥CIN 2 lesions (CIN 2, CIN 3 and CIS) than in ≤CIN 1 lesions (CIN 1, normal, reactive and metaplastic), in both pre- and post-fortification CIN 3/CIS specimens. Age- and race-adjusted mean H3 Lys-9 score was significantly higher in all cell or lesion types in CIN 3/CIS specimens obtained in the post-fortification period compared to pre-fortification period (P < 0.05, all comparisons). In contrast, in specimens obtained from women free of CIN, Lys-9 methylation in normal/reactive cervical epithelium was significantly lower in post-fortification specimens than in pre-fortification specimens (P = 0.03).Conclusions: Higher levels of Lys-9 methylation in ≥CIN 2 compared to ≤CIN 1 lesions suggest that higher Lys-9 methylation is associated with progression of lower grade CIN to higher grade CIN. Higher Lys-9 methylation in cervical tissues of women diagnosed with CIN 3 in the postfortification period than in pre-fortification period suggest that fortification may adversely affect histone methylation in already initiated cells. Lower Lys-9 methylation in normal/reactive cervical cells of women free of CIN in the post-fortification period than pre-fortification on the other hand suggests that fortification is likely to protect against initiation of carcinogenic process in the cervix. These results suggest that mandatory fortification with folic acid in the US seems to have different effects on cancer depending on the stage of carcinogenesis. Because this is the first study to report folic acid fortification-associated differences in histone methylation and because of the limitations inherent to the approach we have taken to demonstrate these differences, validation of the results in other study populations or with other techniques for assessing histone methylation is necessary.Keywords: folic acid, fortification, histone methylation, cervix